Janice VanCleave's oceans for every kid : easy activities that make learning science fun. - VanCleave, Janice Pratt (VanCleave, Janice Pratt. Janice VanCleave science for every kid series., 1996)
Includes information on techniques and technologies of oceanography, the topology of the ocean floor, movement of the sea, properties of sea water, and life in the sea.